1984
DOI: 10.1128/jb.158.3.890-896.1984
|View full text |Cite
|
Sign up to set email alerts
|

Transposon mutagenesis of marine Vibrio spp

Abstract: MATERIALS AND METHODSReagents, enzymes, and DNA analysis. Antibiotics were purchased from Sigma Chemical Co., St. Louis, Mo., and were used at the following concentrations: tetracycline, 20 ,ug/ml for Escherichia coli and 10 ,ug/ml for Vibrio spp.; ampicillin, 80 ,ug/ml; chloramphenicol,20 ,ug/ml; kanamycin, 80 ,ug/ml. Restriction endonucleases were purchased from New England BioLabs, Inc., Boston, Mass. T4 DNA ligase was purchased from Bethesda Research Laboratories, Rockville, Md. Conditions for restrictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Twenty/zl of 1 mM sterile CaCI 2 solution and 100 t~l chloroform was added and after vortexing for 1 min the lysate was centrifuged at 8000 × g for 20 rain. The supernatant containing a portion of PlclrlOOCM transducing particles packaged with mini-Mu (Tet r) DNA [12], was transferred to a new tube and stored at 4"C.…”
Section: Preparation Of Pl-mini-mu (Tet') Co-lysatementioning
confidence: 99%
See 2 more Smart Citations
“…Twenty/zl of 1 mM sterile CaCI 2 solution and 100 t~l chloroform was added and after vortexing for 1 min the lysate was centrifuged at 8000 × g for 20 rain. The supernatant containing a portion of PlclrlOOCM transducing particles packaged with mini-Mu (Tet r) DNA [12], was transferred to a new tube and stored at 4"C.…”
Section: Preparation Of Pl-mini-mu (Tet') Co-lysatementioning
confidence: 99%
“…Mu phage mutagenesis has successfully been used to obtain lac fusion mutants of E. coil and S. typhimurium and bacterial gene regulation studies have benefited greatly from analysis of such mutants ~7, [9][10][11]. Belas et al [12] previously reported the use of the PlclrlOOCM phage for mobilization of their newly constructed mini-Mu (Tet r) transposon into the genome of Fibrio parahaemolyticus. This transfer system was tested with Fibr/o sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three V. parahaemolyticus strains were used as follows: EMS 13-028/A3 (EMS) (Han, Tang, Pantoja, et al 2015;Han, Tang, Tran et al 2015), RIMD2210633 (RIMD) (Makino et al 2003) and LM5312 (LM) (Belas et al 1984;McCarter 1998). The bacteria were grown at 30°C in trypticase soy broth or on 1.5% trypticase soy agar (Becton Dickinson and Company, Spark, MD, USA) supplemented with an additional 2% NaCl (TSB2+) to make the overall salinity 25 parts per thousand (ppt) matching the salinity of the water used for housing the shrimp.…”
Section: Bacterial Strains and Mediamentioning
confidence: 99%
“…RIMD2210633 (RIMD) is a human clinical isolate obtained in 1996 from a patient with 'travellers' diarrhoea' at the Kansai International Airport, Japan (Makino, Oshima, Kurokawa, Yokoyama, Uda, Tagomori, Iijima, Najima, Nakano, Yamashita, Kubota, Kimura, Yasunaga, Honda, Shinagawa, Hattori & Iida 2003). LM5312 (LM), also known as BB22OP, is an environmental strain that was obtained from Bangladesh in the early 1980s (Belas, Mileham, Simon & Silverman 1984;McCarter 1998). In addition to the comparative strain analysis, pathogenicity of the EMS strain of V. parahaemolyticus to shrimp at different inoculation levels was examined to establish a disease challenge assay.…”
Section: Introductionmentioning
confidence: 99%